A new tribe, genus, and species of freshwater mussel from the Changjiang River Basin in China (Bivalvia, Unionidae, Unioninae) - Yu-Ting Dai; Zhong-Guang Chen; Shan Ouyang; Xiao-Chen Huang; Xiao-Ping Wu (Zoosystematics and Evolution)
A new tribe, genus, and species of freshwater mussels, Globunionini Dai, Chen, Huang & Wu, tribe nov. and Globunio mirificus Chen, Dai, Huang & Wu, gen. et sp. nov., is described from the Changjiang River Basin in China based on comparative morphology and molecular phylogeny. The species presence of a special small-sized and elongated globular, which distinguishes it from all other tribes. The discovery increases the diversity of freshwater mussels in the Changjiang River Basin.